AKSESIBILITAS WEBSITE PEMERINTAH KOTA JAYAPURA OLEH MASYARAKAT KOTA JAYAPURA - Andi Gita Novianti; Margareth D. A. Widirahayu (DINAMIS, 2015)
The increasing number of Internet users in Indonesia in line with development incommunication technology which is facilitates the information of searching process. Thisencourages the Government to follow the trend by providing access to free informationthrough the website which is also pushing the speed and transparency of public information.Through www.jayapurakota.go.id, Jayapura City Government wanted to disclose informationto the public.This study aims to determine the accessibility of Jayapura City Government websitewww.jayapurakota.go.id. Results from this research can add scholarly study on informationtechnology and mass communication, especially in new media or the Internet. In addition theresults of this study can give a recommendation for government, especially the Jayapura CityGovernment for further innovative in providing information by the public needs.The method used is descriptive method with data collection through questionnairesdistributed to 100 respondents who live in the city of Jayapura to collect their opinions andperceptions regarding Jayapura city government website. The research also includesmethods of software testing Black-box that is used to measure the performance of a websitein order to know the technical causes of the website which affects the level of satisfaction ofthe people in accessing information through the website